Analysis of Human Error Probability at Shipyard Using Human Error Assessment and Reduction Technique (HEART) - Fanny Octaviani; Mohammad Danil Arifin (International Journal of Marine Engineering Innovation and Research, 2024)
In shipyards, human error is a serious problem that can compromise operational effectiveness, productivity, and safety. The effectiveness of shipyard operations still largely depends on human participation, despite the quick advances in automation and technology. In shipyards, human error can result in mishaps, monetary losses, and reputational harm. Finding workable solutions is therefore essential to lowering the possibility of human error. The possibility of human error in shipyards is investigated in this article by first determining the variables that may lead to errors and then estimating the likelihood that they will occur. The Human Error Assessment and Reduction Technique (HEART) is the methodology employed. A technique called HEART is used to assess the degree of human error in a system, which helps to analyze how human errors affect a system's performance. The analysis's findings show that bending and pressing plates are two fieldwork tasks that have a high risk of human error. This study also makes it clear that management’s engagement in resolving human error issues must be proactive. Hands-on training, ongoing safety policy formulation, and encouragement of a happy workplace are just a few ways that management can help lower the possibility of human error.